2022
DOI: 10.3390/polym14235232
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene Pipe Compounds with Varying Post-Consumer Packaging Recyclate Content

Abstract: The high recycling targets set by the European Commission will create an increased availability of polypropylene (PP) post-consumer recyclates (PCRs). However, no regulations mandate the use of recycled PP (rPP), so the industry is challenged to explore possibilities to utilize such materials. One option, as suggested by the European Commission, is the introduction of rPP in pipe applications. According to existing standards, the use of recyclate is not allowed in pressurized gas and drinking water systems. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…For warm drawing or thermoforming, the strain at break (which would relate more to a cold drawing) is also not a critical design parameter. Furthermore, the strain at break value highly depends on the injection molding conditions and MFR or rather orientation due to injection molding [ 13 , 14 ], as well as inclusions within the specimen which lead to premature fracture at lower strains and give an indication of the contamination of the compounds. vPP, rPP-A, and rPP-B, as well as all compounds from these materials, show relatively low strain at break values of between 44% and 71%, as can be seen in Figure 6 c. Only rPP-C (277%) and the compound C55 (176%) achieve much higher strain at break values suggesting fewer unknown inclusions in rPP-C than in rPP-A and rPP-B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For warm drawing or thermoforming, the strain at break (which would relate more to a cold drawing) is also not a critical design parameter. Furthermore, the strain at break value highly depends on the injection molding conditions and MFR or rather orientation due to injection molding [ 13 , 14 ], as well as inclusions within the specimen which lead to premature fracture at lower strains and give an indication of the contamination of the compounds. vPP, rPP-A, and rPP-B, as well as all compounds from these materials, show relatively low strain at break values of between 44% and 71%, as can be seen in Figure 6 c. Only rPP-C (277%) and the compound C55 (176%) achieve much higher strain at break values suggesting fewer unknown inclusions in rPP-C than in rPP-A and rPP-B.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility for modifying rPP could be compounding with virgin polymers. While there is research available for other applications [ 13 , 14 , 15 ], no preceding research could be found for creating and assessing thermoforming compounds with post-consumer recyclate content.…”
Section: Introductionmentioning
confidence: 99%
“…Pipe materials are known for their very low MFR values as it is required by several standards in the pipe industry [ 4 ]. The MFR values of PP pipe grades are usually in the range of 0.25 to 4.5 g/10 min [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The targeted property adjustment of recyclates by blending with virgin materials opens many areas of application that were previously not possible due to the initial properties of recyclates. Nevertheless, the long-term behavior of recycled materials must not be ignored, as there are still considerable deficits in this area [ 3 , 4 , 5 ]. Depending on the intended property profile and whether the recyclate or the virgin material should be the main component, the right blending ratio must be selected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation